EFFECT OF HR POLICIES, EMPLOYEE COMMITMENT AND REMOTE WORKING ON ORGANIZATIONAL PERFORMANCE (Study on Collaborative Education Units in Indonesia) - Lukitasari, Dewi Diana (FEB Universitas Sam Ratulangi Manado, 2024)
This research aims to analyze the effect of HR Policies, employee commitment, and remote working on organizational performance in Collaborative Education Units (SPK) in Indonesia. The method used in this research is a quantitative descriptive method. The population in this study consisted of employees who worked at education unit schools in Indonesia. The data analysis model uses Structural Equation Modeling (SEM) with a sample of 190 people. The analysis technique in this research is Partial Least Square (PLS), using the smartPLS 3.0 program to test the hypothesis. The research results show that HR Policies positively and significantly affect organizational performance. Employee commitment has a positive and significant effect on organizational performance. Remote working has a positive and significant effect on organizational performance.